Perancangan Sistem Informasi Akuntansi Revenue Cycle dan Inventory Pada PT XYZ - Sundjaja, Arta Moro; Kristianto, Yudhi (ComTech: Computer, Mathematics and Engineering Applications, 2010)
PT XYZ is a trading company in electronic equipment distributor of Philips, that needs accounting information system in developing system ongoing manual to be a computerized one. The research method used is analysis method and object-oriented analysis and design (OOAD). The data collecting is through survey of the ongoing system and also interview based on supported theories, which gathered from the books about analysis and system design. The design method is through designing suggested system model. The expected result is sales accounting information system, cash income, and other feature to help PT XYZ in doing events. The result from this research is this information system application could help reduced data searching error transaction by employees. Especially, in reducing errors caused by data record error transaction by employees. This is purposed to every employee could be more focus in doing the events and more responsible in every acts.